Simple lessons, quick results : essential tips and tricks for drawing people - Hart, Christopher, 1957- (Hart, Christopher, 1957- Drawing with Christopher Hart., 2018)
This is the easy way to learn how to draw people! Chris Hart offers straightforward instruction designed to solve common figure-drawing problems that aspiring artists encounter. His accessible, practical techniques include focusing on the bodys natural curves, as opposed to drawing muscles, and breaking the torso down into three distinct, understandable areas. With this book, anyone can immediately grasp the basicsand create the art to prove it!